Gestational weight gain during the second and third trimesters and adverse pregnancy outcomes, results from a prospective pregnancy cohort in urban Tanzania - Jiaxi Yang; Molin Wang; Deirdre K. Tobias; Janet W. Rich-Edwards; Anne Marie Darling; Ajibola I. Abioye; Andrea B. Pembe; Isabel Madzorera; Wafaie W. Fawzi (BMC, 2022)
Plain language summary Pregnancy is a critical lifetime event for both mother and the offspring, with implications in short-term and long-term health consequences. Gestational weight gain (GWG) is an important modifiable factor for pregnancy outcomes related to infant body size and weight and prematurity. Countries in sub-Saharan Africa (SSA) have long had poor rates of insufficient GWG and pregnancy complications associated with insufficient GWG. Nevertheless, some SSA countries are experiencing economic transitions accompanied with changes in lifestyle and nutrition, which might impact pregnancy experiences, including GWG and pregnancy outcomes. This study aimed to characterize recent GWG patterns and the associations of both inadequate and excessive GWG with adverse pregnancy outcomes, using an urban pregnancy cohort in Tanzania. This study found that 42.0%. 22.0%, and 36.0% of women had insufficient, adequate, and excessive GWG, respectively. Insufficient GWG was associated with higher risks of small infant size and low infant body weight, and excessive GWG was associated with higher risk of preterm birth, particularly among women with body mass index 18.5-25.0 kg/m2. Results from the present study highlight that both insufficient and excessive GWG are of potential public health concerns in urban centers of SSA, concerning upward trends in obesity and possibly obesity-related pregnancy consequences. Local public health practitioners should continue to advocate longitudinal GWG monitoring and care among African pregnant women, and optimal GWG with feasible and effective clinical guidelines should be developed to prevent both over- and under-gaining of maternal weight during pregnancy.